Salbutamol and ipratropium in acute asthma. Issue 8 (August 1987) - Rayner, R J; Cartlidge, P H; Upton, C J
Abstract : Thirty seven children with acute asthma were given nebulised ipratropium or placebo 30 minutes after their first dose of salbutamol and eight hourly thereafter. There were no significant differences between the two groups in clinical scores, peak expiratory flow rates, length of stay in hospital, or the need for oral steroids.